2017
DOI: 10.1002/gj.2993
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic processes and mechanisms for collision to post‐orogenic extension in the Western Dabie Orogen: Insights from numerical modeling

Abstract: Post‐orogenic extension is the last stage of a tectonic process towards the end of each Wilson cycle in both ancient and modern continental collisional zones, but their dynamics, controlling factors, and roles for the post‐orogenic extension processes remain debatable. We present the first two‐dimensional thermo‐mechanical numerical model of double sutures inspired by the Western Dabie Orogen to investigate the dynamics of post‐orogenic extension. Our results indicate that the pro‐continent re‐subduction can d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The flat‐slab subduction is generally not stable and will evolve to the normal/steep subduction finally by either slab rollback or delamination. In addition, a segment of slab break‐off may also occur during and after flat‐slab subduction (Axen et al, 2018; Dai et al, 2017; Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flat‐slab subduction is generally not stable and will evolve to the normal/steep subduction finally by either slab rollback or delamination. In addition, a segment of slab break‐off may also occur during and after flat‐slab subduction (Axen et al, 2018; Dai et al, 2017; Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Slab rollback, which is driven by mantle flow pressure gradients or negative buoyancy anomalies, that is, from slab eclogitization (Nakakuki & Mura, 2013), has been proposed as the mechanism for the tectono‐magmatic evolution of the overriding plate after flat‐slab subduction in the Lhasa Terrane (Yang et al, 2018), the North China Craton (Wu et al, 2019), and the southwestern Gondwana (Navarrete et al, 2019). Slab delamination, which can be triggered by a lithospheric weak layer (Li et al, 2014; Liao et al, 2017) or gravitational instabilities such as the presence of eclogite (Dai et al, 2017; Z.‐H. Li et al, 2016, 2019), involves the foundering of the cratonic lithosphere into the asthenospheric mantle.…”
Section: Introductionmentioning
confidence: 99%
“…The most likely reason for the fast slab retreat rates of our models at developing stage is the steep subducting slab dip angle, which provides more downgoing force to accelerate the subduction. Another reason might be in part due to more hot mantle upwellings into the neck and the stretched underlying continental lithosphere, which favours to accelerate thinning and weakening the continental slab, eventually leads to fasten back‐arc extension and the slab retreat (Dai, Li, Li, Somerville, & Liu, ; Dai et al, ; Sheng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of Yanshanian deformation in Western Shandong by J. Zhang et al () is suggested to mark the transition from Paleo‐Pacific to Pacific Plate subduction. Studies on numerical modelling by Dai, Li, Li, Somerville, and Liu () have been used to explain postorogenic extension in the Western Dabie Orogen. The paper by Zhou et al () discusses the Triassic Orocline in East Asia and the transition from passive margin to foreland basin in Eastern North China Block.…”
Section: Volume 1 Structure and Main Themesmentioning
confidence: 99%